Korelasi Antara General Pedagogy Knowledge dan Praktek Mengajar dengan Efikasi Diri Pada Calon Guru Biologi - Maesaroh Maesaroh; Mega Elvianasti; Irdalisa Irdalisa; Husnin Nahry Yarza (Department of Biology Education, Faculty of Education and teacher Training, Maritime University of Raja Ali Haji, 2021)
This study aimed to analyze the correlation between General Pedagogy Knowledge (GPK) and teaching practice with Self Efficacy of pre-service biology teachers. One of the most essential knowledge to provide pre-service biology teachers General Pedagogy Knowledge (GPK). This knowledge is a significant component of teacher knowledge. GPK will be reflected when pre-service biology teachers practice teaching in the classroom, and they will be supported by good Self Efficacy. In this research, self-efficacy is a pre-service biology teacher's beliefs in her ability to choose the right learning strategy when teaching practice (microteaching). The research used is the descriptive correlation method with a multiple regression approach. A total of 30 pre-service biology teachers were selected as the research sample used the purposive sampling technique. The research instruments used the RPP assessment rubric, teaching practice assessment rubric and self-efficacy questionnaire. The data obtained were analyzed using SPSS 26. Based on the test results by comparing the value of r (table) using a 5% significance level of 0.453 and r (count) obtained 0.673, there is a significant correlation between General Pedagogy Knowledge and teaching practice with Self Efficacy of pre-service biology teachers. It can be concluded that mastery of General Pedagogy Knowledge and good teaching practices can increase the Self Efficacy of pre-service biology teachers.